P200 Acceptability of a brief fatigue intervention for patients with inflammatory arthritis: a qualitative process evaluation. (26th April 2021) - Berry, Alice; Bridgewater, Susan; Abbott, Bryan; Adams, Jo; Dures, Emma
Abstract: Background/Aims   Patients with inflammatory arthritis report fatigue as a primary symptom that affects everyday life. FREE-IA (Fatigue - Reducing its Effects through individualised support Episodes in Inflammatory Arthritis) is a feasibility study of a brief intervention (2-4 sessions of 20-30 minutes) designed to reduce fatigue impact. The intervention designed with patients and health professionals is delivered by rheumatology practitioners in one-to-one sessions, after training and using a manual. The aim of this process evaluation was to understand the perspectives of patients and practitioners in FREE-IA. Methods   One-to-one telephone interviews were conducted with patients who had received the intervention and practitioners who had delivered it. Interviews were audio-recorded, transcribed and anonymised. An inductive thematic analysis approach was used to identify and analyse patterns within each data set. Results   Twenty-two patients, and eight practitioners across the five sites participated. We identified four patient and three practitioner themes. Patient themes: Collaborative, non-judgemental consultations: participants reported positive relationships in which their fatigue was validated, and they were able to reflect. They expressed their preference for a responsive, flexible approach to sessions, rather than a rigid, 'protocolised' approach. Relevant and useful, but not ground-breaking: participants appreciated the opportunity to tailor content to their individual priorities. They found it helpful to visualise fatigue and identified daily dairies as useful. Although the content was not seen as ground-breaking, it provided focus. Insights and self-awareness: sessions increased participants' awareness of lifestyle factors and patterns influencing their fatigue, which increased their sense of control and confidence to manage fatigue. Degrees of openness to change: sessions prompted some participants to engage in positive behaviour change or make plans for changes. However, some participants expressed frustration, explaining that it was not the right time because their lives were complicated. Practitioner themes: Engagement with the intervention: practitioners liked training face-to-face with peers and their enjoyment of the intervention increased with experience of delivery. However, for practitioners with extensive experience of providing fatigue support, the low level of treatment intensity and the manualised approach limited the perceived usefulness of the intervention. Research versus clinical practice: practitioners expressed concern about fitting sessions into clinic appointments, and it was often a challenge to offer patients a follow-up session within the proposed two-week time frame. Collaborating with patients: practitioners reported that many patients were willing to try the tools and strategies. While some practitioners followed the manual in a linear way, others used it more flexibly. Conclusion   There is potential for this brief fatigue intervention to benefit patients. Future research will focus on flexibility to fit with local services and creating educational learning resources for practitioners to use in a range of contexts. Disclosure   A. Berry: None. S. Bridgewater: None. B. Abbott: None. J. Adams: None. E. Dures: None.